Christian Orthodox Migrants in Western Europe Secularization and Modernity through the Lens of the Gift Paradigm - Hämmerli, Maria (Routledge Studies in Religion, 2023)
Christian Orthodox Migrants in Western Europe: Secularization and Modernity through the Lens of the Gift Paradigm explores a religious community that has been getting increasing scholarly attention. While most of the literature in the field looks at this religious tradition in terms of its alleged inability to come to terms with modernity - due to its specific religious institutions, practices and dogma - this book takes a step back from such Western-centered and Protestant-biased analysis of religion. It addresses Orthodoxy's recent encounter with the West, modernity and secularization in the process of post-communist migrations from Eastern Europe, revealing the complicated identity redefinition and re-compositions of a religious group that highly values continuity, tradition and ethnic/national belonging. Using socio-anthropological qualitative research on Romanian, Russian, Greek and Serbian Orthodox migrants in Western Europe in a comparative perspective, this volume grasps the interplay between the institutional and the individually lived aspects of religion in their relation to the increasingly secular ""conditions of belief"" in Western European host countries. This book is important for those studying or researching Orthodox Christianity, religion and migration, secularization and modernity, as well as those in related disciplines such as sociology, anthropology of religion, religious studies, political science, migration studies and cultural studies.